A INFLUÊNCIA DOS EVENTOS EXTERNOS EM PROL DO DESENVOLVIMENTO SUSTENTÁVEL NA ADAPTAÇÃO ESTRATÉGICA DAS CORPORAÇÕES - UM ESTUDO MULTICASO DA INDÚSTRIA DO PETRÓLEO MUNDIAL - - Figueiredo, Cristina Brunet de (2011)
This multi case study seeks to verify how the process of strategic change and adaptation, characterized as a continuous process based on three essential dimensions (content, internal and external contexts, and the change process) has ocurred in the global oil industry in recent years, as a reaction or adjustment to major external events on sustainable development (external context), ocurred between 1997 and 2009. Initially, it was performed a literature review on the theoretical foundations related to strategy, administration and change management, as well as the analysis of concepts of stakeholders and their applications, sustainable development and sustainability. Subsequently, using the information captured from the sustainability reports published by six international oil companies, a descriptive research and the analysis of the industry response to the selected external events were conducted. Based on the intersection of the companies reactions and responses, described in their sustainability reports, with the selected external events, it was possible to verify and show the process of strategic adaptation of the six companies examined, both in environmental, social and management dimensions, both immediately after the event and over time.